Relationship between damage‐associated molecular patterns and cytokines in myasthenia gravis. Issue 4 (24th August 2016) - Uzawa, Akiyuki; Kanai, Tetsuya; Kawaguchi, Naoki; Oda, Fumiko; Ozawa, Yukiko; Himuro, Keiichi; Kuwabara, Satoshi
Abstract: Objective: Damage‐associated molecular patterns (DAMP) and cytokines can play a crucial role in inflammation at neuromuscular junctions in myasthenia gravis (MG). However, the relationship between DAMP and cytokine levels in MG pathogenesis remains unknown. To clarify this, we examined the relationship between serum levels of DAMP and cytokines in MG patients. Methods: Using serum data from 26 patients with anti‐acetylcholine receptor antibody‐positive MG, we investigated the relationship between the levels of DAMP (high‐mobility group box 1 [HMGB1] and peroxiredoxin 5) and cytokines (interleukin [IL]‐4, IL‐15, IL‐19, IL‐20, IL‐28A, IL‐35, a proliferation‐inducing ligand [APRIL] and vascular endothelial growth factor), which were reported to be significantly elevated in MG. Results: Serum levels of APRIL ( r = 0.4789, P = 0.0133), IL‐19 ( r = 0.5496, P = 0.0036) and IL‐35 ( r = 0.5396, P = 0.0044) were correlated with those of HMGB1, but no cytokine levels were correlated with peroxiredoxin 5 levels. When we carried out multivariate analyses, only APRIL ( P = 0.0244) and IL‐19 ( P = 0.0009) levels were correlated with HMGB1 levels. Conclusions: HMGB1 might be related with upregulation of IL‐19 and APRIL levels in MG immunopathogenesis. These molecules could play a key role in controlling autoimmune inflammatory response, and represent a potent therapeutic target in MG. Abstract : HMGB1 may be related with upregulation of IL‐19 and APRIL levels in MG immunopathogenesis.